2007
DOI: 10.1016/j.fertnstert.2006.11.098
|View full text |Cite
|
Sign up to set email alerts
|

Human myometrium and leiomyomas express gonadotropin-releasing hormone 2 and gonadotropin-releasing hormone 2 receptor

Abstract: A second form of GnRH and corresponding receptor exists in the fibroid and myometrium. We speculate that an autocrine loop exists. Our findings provide further evidence that GnRH agonists may interact directly with GnRH receptors present in uterine fibroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…A recent study demonstrated that leuprolide acetate may act directly on fibroids by an increase in the ECM genes, COL1A1, fibronectin, and veriscan variant 0, followed by return to normal after five days of treatment (as discussed by [80]). These findings were supported by the presence of GnRH receptors in uterine fibroid and subject-matched myometrium (as discussed by [81]). Similar to the concept of reciprocity for mechanical stress, hydration of the ECM requires an osmotic response regulated by the transcription factor, nuclear factor of activated T cells-5 (NFAT5) that coordinates expression of hyperosmolarity response genes, such as aldose reductase and sodium myoinositol transporter 1 (SMIT), all of which were increased in fibroid cells, compared to myometrial cells (as discussed by [82]).…”
Section: Extracellular Matrix Of Uterine Fibroidssupporting
confidence: 57%
“…A recent study demonstrated that leuprolide acetate may act directly on fibroids by an increase in the ECM genes, COL1A1, fibronectin, and veriscan variant 0, followed by return to normal after five days of treatment (as discussed by [80]). These findings were supported by the presence of GnRH receptors in uterine fibroid and subject-matched myometrium (as discussed by [81]). Similar to the concept of reciprocity for mechanical stress, hydration of the ECM requires an osmotic response regulated by the transcription factor, nuclear factor of activated T cells-5 (NFAT5) that coordinates expression of hyperosmolarity response genes, such as aldose reductase and sodium myoinositol transporter 1 (SMIT), all of which were increased in fibroid cells, compared to myometrial cells (as discussed by [82]).…”
Section: Extracellular Matrix Of Uterine Fibroidssupporting
confidence: 57%
“…These menopause-like symptoms limit applicability to short-term therapy. Prior studies have demonstrated extrahypothalamic presence of GnRH receptors in mammalian reproductive tissues (33,34), and in uterine leiomyoma tissues (18,35). These findings suggest that GnRH-a could be used locally to avoid systemic morbidity.…”
Section: Discussionmentioning
confidence: 76%
“…Analysis of microarray data, confirmed by quantitative real-time polymerase chain reaction (PCR) and immunohistochemical studies, reveal the expression of GnRH receptors in leiomyoma and patient-matched myometrium (18). The presence of receptors for GnRH hormones in leiomyomas is further evidenced by the direct regulation of GnRH analogues (GnRH-a) on leiomyoma cell ECM gene expression and protein production in culture (19).…”
mentioning
confidence: 94%
“…Direct activation of the GnRH receptors onˆbroids is presumed to be involved inˆbroid shrinkage. 17 Crow and colleagues suggested that response to GnRHa treatment is aŠected by other histopathological features, including rate of cell proliferation, degree of in‰ammatory cell inˆltration, and density of estrogen receptors. 18 These factors may work to change vascularity as well as volume of theˆbroid, which could make it more di‹cult to predict AUC reduction.…”
Section: Discussionmentioning
confidence: 99%